A microscopic and Synchrotron-based characterization of urban particulate matter (PM 10-PM 2.5 and PM 2.5) from Athens atmosphere, Greece - Godelitsas, A.; Nastos, P.; Mertzimekis, T. J.; Toli, K.; Simon, R.; Göttlicher, J. (Nuclear Instruments and Methods in Physics Research, Section B: Beam Interactions with Materials and Atoms, 2011)
Urban particulate matter (PM 10-PM 2.5 and PM 2.5) from Athens (Greece) atmosphere, primarily investigated by SEM-EDS, was further studied in the FLUO and SUL-X beamlines of ANKA Synchrotron facility (KIT, Germany). The SR μ-XRF study showed both geological (e.g. CaTi, CaK and CaSrKRb) and anthropogenic particles exhibiting heavy metal combinations such as FeCo, FeCoCuV and ZnV. It was also revealed that very hazardous metalloids and heavy metals, namely As and Pb, are concentrated in isolated respirable (PM 2.5) microparticles. It was attempted to investigate the oxidation state of As by means of μ-XANES. The As K-edge XANES spectrum of the sample shows a main peak at about 11.874 keV which matches adequately with the As(V) reference spectrum but part of the As seems to have a lower oxidation state (most probably As(III)). This is the first non-bulk study with regard to the partitioning and solid-state speciation of hazardous chemical elements in urban atmospheric microparticles from greater Athens area, rated as an alpha-world city with a population of ca. 4 million people. © 2011 Elsevier B.V. All rights reserved.
Keywords: Arsenic; Athens; atmosphere; Beam-lines; Chemical elements; Chemical speciation; Earth atmosphere; Fluorescence spectroscopy; Germany; Greece; Hazardous chemicals; Heavy metals; Lead; Metal combination; Metallic compounds; Micro-particles; Oxidation state; Particulate matter; Reference spectrum; SEM-EDS; Synchrotron; Synchrotrons; X ray absorption spectroscopy; X ray fluorescence spectroscopy; X-ray absorption spectroscopy; X-ray fluorescence spectroscopy; XANES; XANES spectra